The Lethal Journey of Brain Eating Amoebae from Nose to Neurons - Kasarla, Rajeswar Reddy (Medical Journal of Eastern Nepal, 2025)
Naegleria fowleri, commonly known as the brain-eating amoeba, is a free-living, thermophilic protozoan, causes primary meningoencephalitis (PAM), which is a rare yet rapidly fatal infection of the central nervous system. N.fowleri is found in warm freshwater bodies, such as lakes, hot springs, poorly chlorinated pools, or tap water. N.fowleri enters the body through the nasal passages during activities such as swimming, diving, or nasal rinsing with contaminated water. This amoeba then crosses the cribriform plate and travels along the olfactory nerve to invade the central nervous system, causing rapidly progressive necrotizing meningoencephalitis. Early symptoms of N.fowleri infection mimic viral or bacterial meningitis, including fever, headache, nausea, and vomiting. These symptoms rapidly progress to confusion, seizures, photophobia, altered mental status, and coma. The disease is fatal in over 98% of cases with a median survival of just 5 days after symptom onset. PCR is the gold standard for definitive diagnosis. CSF findings resemble those of bacterial meningitis, showing elevated white blood cells, low to normal glucose, elevated protein, and increased opening pressure. Diagnosis is challenging due to nonspecific symptoms resembling viral or bacterial infections. Prompt recognition, accurate diagnosis, and aggressive combination therapy are crucial for improving outcomes, although fatality rate is very high. N.fowleri infection poses a serious public health concern due to lack of vaccines and effective treatment. The knowledge and scientific information on N.fowleri infection is still relatively limited to many clinicians, and received little attention; hence this comprehensive review of N.fowleri infection is undertaken to highlight its importance and further research.